Trehalose Augments Neuron Survival and Improves Recovery from Spinal Cord Injury via mTOR-Independent Activation of Autophagy. (12th July 2021) - Zhou, Kailiang; Chen, Huanwen; Xu, Huazi; Jia, Xiaofeng
Abstract : Spinal cord injury (SCI) is a major cause of irreversible nerve injury and leads to serious tissue loss and neurological dysfunction. Thorough investigation of cellular mechanisms, such as autophagy, is crucial for developing novel and effective therapeutics. We administered trehalose, an mTOR-independent autophagy agonist, in SCI rats suffering from moderate compression injury to elucidate the relationship between autophagy and SCI and evaluate trehalose's therapeutic potential. 60 rats were divided into 4 groups and were treated with either control vehicle, trehalose, chloroquine, or trehalose + chloroquine 2 weeks prior to administration of moderate spinal cord crush injury. 20 additional sham rats were treated with control vehicle. H&E staining, Nissl staining, western blot, and immunofluorescence studies were conducted to examine nerve morphology and quantify autophagy and mitochondrial-dependent apoptosis at various time points after surgery. Functional recovery was assessed over a period of 4 weeks after surgery. Trehalose promotes autophagosome recruitment via an mTOR-independent pathway, enhances autophagy flux in neurons, inhibits apoptosis via the intrinsic mitochondria-dependent pathway, reduces lesion cavity expansion, decreases neuron loss, and ultimately improves functional recovery following SCI (all p < 0.05 ). Furthermore, these effects were diminished upon administration of chloroquine, an autophagy flux inhibitor, indicating that trehalose's beneficial effects were due largely to activation of autophagy. This study presents new evidence that autophagy plays a critical neuroprotective and neuroregenerative role in SCI, and that mTOR-independent activation of autophagy with trehalose leads to improved outcomes. Thus, trehalose has great translational potential as a novel therapeutic agent after SCI.